2019
DOI: 10.1016/j.mjafi.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory parameters at rest after months of stay at 3300 m: A comparison between acclimatized lowlanders and natives at Leh

Abstract: Background: Increased pulmonary ventilation helps lowlanders and natives to maintain arterial oxygenation at high altitudes. Natives of Ladakh have been shown to have similar ventilatory parameters as Tibetans at 3300 m. But there is limited literature comparing these parameters in Ladakhi natives with acclimatized lowland sojourners.Methods: End-tidal carbon dioxide partial pressure (EtCO 2 ), blood oxygen saturation (SpO 2 ) and hemoglobin concentration (Hb) were measured in 276 participants, 126 native high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…After >25,000 years of life living at an altitude of 4,000 m, the Tibetan people have mutations in the EGLN1 and EPAS1 genes. These 2 genes participate in the hypoxia-inducible factor transcription pathway and mediate the human body’s response to hypoxia [21], which ultimately result in the upregulation of a considerable number of target genes that aid during the adaptation to hypoxia, including the erythropoietin gene (resulting in the generation of more red cells) and vascular endothelial growth factor gene (resulting in the generation of more blood vessels). In addition, some genes are downregulated, such as pyruvate dehydrogenase kinase 1, leading to decreased mitochondrial oxygen consumption [22].…”
Section: Discussionmentioning
confidence: 99%
“…After >25,000 years of life living at an altitude of 4,000 m, the Tibetan people have mutations in the EGLN1 and EPAS1 genes. These 2 genes participate in the hypoxia-inducible factor transcription pathway and mediate the human body’s response to hypoxia [21], which ultimately result in the upregulation of a considerable number of target genes that aid during the adaptation to hypoxia, including the erythropoietin gene (resulting in the generation of more red cells) and vascular endothelial growth factor gene (resulting in the generation of more blood vessels). In addition, some genes are downregulated, such as pyruvate dehydrogenase kinase 1, leading to decreased mitochondrial oxygen consumption [22].…”
Section: Discussionmentioning
confidence: 99%
“…With decades of experience in deployment at these altitudes, the doctors of the Indian Armed Forces have developed a remarkable body of knowledge on matters related to health at altitude. A case series on imaging modalities for cerebrovascular thrombosis is being published in this issue; Sikri et al 13 have reported on a nuanced study of a variation of the time-tested acclimatization schedule followed in inducting troops to the higher altitudes in mountainous regions, and Dua et al 14 have compared acclimatized lowlanders with natives of the Himalayan heights.…”
mentioning
confidence: 99%